AS PRAÇAS DA CIDADE DE PONTA GROSSA-PR: ARBORIZAÇÃO URBANA, INFRAESTRUTURA E DISTRIBUIÇÃO ESPACIAL. - Eurich, Zíngara Rocio dos Santos (2014)
According to the importance of public spaces, especially parks, both for city population and the urban environment, this research aims to analyze the conditions of the squares of the city of Ponta Grossa-PR. For that there were used methodologies which were capable of evaluate qualitative and quantitative the afforestation and infrastructure of squares and to analyze the spatial aspects, checking the morphology, typology, distribution and functionality of these spaces, in order to promote and enhance the public open spaces of the city. Regarding the spatial distribution of the squares it was found that the concentration of them are presented in the central area of the city, and the downtown area has the highest Index for Quarter Square (IAPB), with 4.25%. While verified the morphology of the squares, it was observed that most of them 30.1% has the rectangular shape. Some areas considered as squares by the City Hall of Ponta Grossa are shown as an area without direct social function, and 83.1% could be considered effectively as squares. The most common function in the squares is the passive leisure (92.6%). In the survey of afforestation there were accounted 2,369 individuals, which 55.56% are from exotic origin. Regarding the infrastructure, the roads (85.71%), lighting (79.76%) and banks (69.05%) were the most frequent structures in squares. From the results, it is observed that there is a heterogeneous scenario in all analyzed items, since there are squares that have an extensive infrastructure and some areas have no equipment available to the population.